The Influence Of Compensation, Physical Work Environment, Organizational Climate On Performance With Work Motivation As An Intervening Variable On Workers In DKI Jakarta - Mitha Susanto; Rezi Erdiansyah (Green Publisher Indonesia, 2024)
This research investigates the relationship between compensation, physical work environment, and organizational climate with the work motivation and performance of labor employees in DKI Jakarta. Using quantitative methods and a cross-sectional descriptive approach, data was collected from 340 respondents via an online questionnaire. The results of analysis using Structural Equation Modeling (SEM) show that the physical work environment and organizational climate have a significant positive influence on employee performance, while compensation does not have a significant influence. However, work motivation is proven to have a significant positive influence on employee performance. These results imply that it is important for companies to pay attention to the physical work environment, organizational climate, and work motivation to improve employee performance. Suggestions for further research include increasing exploration and adding mediating variables.